Activity of Trigonella foenum-graecum on Some Cell Lines. - Agustini, Kurnia; Sumaryono, Wahono; Widyanto, R Micho (Indonesian Research Gateway, 2011)
TrigonellaÃÂ foenum-graecumÃÂ (TFG)ÃÂ isÃÂ oneÃÂ ofÃÂ medicinalÃÂ plantsÃÂ containsÃÂ some steroidal sapogeninÃÂ such as diosgenin, yamogenin, gitogenin, tigogenin and trigoneoside, alsoÃÂ alkaloidÃÂ trigonellin,ÃÂ whichÃÂ isÃÂ haveÃÂ manyÃÂ activityÃÂ asÃÂ antidiabetic,ÃÂ estrogenicÃÂ andÃÂ also asÃÂ antiÃÂ cancer.ÃÂ ÃÂ ÃÂ ThisÃÂ experimentÃÂ wasÃÂ doneÃÂ toÃÂ exploreÃÂ theÃÂ activityÃÂ ofÃÂ someÃÂ extractÃÂ of TFG on some cell lines such as MCF7 (Human Breast Cancer Cell-line), T47D (Human BreastÃÂ CancerÃÂ Cell-line),ÃÂ PC3ÃÂ (HumanÃÂ ProstateÃÂ Cell-line)ÃÂ andÃÂ SKOVÃÂ (HumanÃÂ Ovarian Carcinoma Cell-line).ÃÂ This assay was done using MTT (3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium)ÃÂ methods.ÃÂ ÃÂ ÃÂ ResultsÃÂ showedÃÂ thatÃÂ ethylÃÂ acetateÃÂ fractionÃÂ givesÃÂ the lowestÃÂ IC50ÃÂ thanÃÂ anotherÃÂ extracts.ÃÂ IC50ÃÂ forÃÂ PC3ÃÂ isÃÂ 66.24ÃÂ ppm,ÃÂ IC50ÃÂ forÃÂ MCF7ÃÂ isÃÂ 41.81 ppm,ÃÂ IC50ÃÂ forÃÂ T47DÃÂ isÃÂ 58.63ÃÂ ppm.ÃÂ ÃÂ ÃÂ TheseÃÂ datasÃÂ canÃÂ beÃÂ usedÃÂ forÃÂ furtherÃÂ researchÃÂ to isolate the active compound from TFG. Keywords: Trigonella foenum-graecum, MCF-7, T47D, SKOV, PC3.